Bank mergers : a local perspective. - Chung, Kwok Hoe. (2008)
This project examines the post merger effects of two local bank mergers in Singapore - DBS and Keppel TatLee. A set of 13 financial ratios was used to determine if the proposed synergistic benefits of mergers were achieved.